Developing business strategy for pt katarda indo global to sustain in indonesia tourism industry - Inassa, Dhini; Rudito, Priyantono (The Indonesian Journal of Business Administration, 2019)
Abstract. PT KATARDA INDO GLOBAL has been operating in the tourism industry running for four years and can be categorized as a new company and is one of the travel agents in Bandung. Who professionally offers the best services â€” along with the times, accompanied by increasingly advanced technological developments, such as the presence of the internet and all digital access in various activities. People can only make transactions such as buying goods, ordering travel tickets, or sending money using a smartphone. This also affected the tourism industry, where conventional travel agents have begun to be replaced with online travel agents such as Traveloka, Pegipegi.com, Tiket.com, and other online travel bookings or other online travel agents. With this, the impact of the business of PT KATARDA INDO GLOBAL is where there has been a decline in revenue in the past year and a lack of brand image in the company. This study aims to analyze the business situation both internally and externally in the tourism industry, especially in tourism and travel; Resource-based views do internal analysis, business models, VRIN analysis, and value chain analysis. While the external analysis was carried out based on PESTEL analysis consisting of Political Factors, Economic Factors, Social Factors, Technology Factors, Environmental Factors, and Legal Factors. Besides, analysis of five of Porter's strengths, and competitor analysis, and SWOT Analysis concluded the two analyzes. The research method used was qualitative, where Focus Group Discussion (FGD) was used by management and customers of PT KATARDA INDO GLOBAL after conducting interviews with partners from hotels, restaurants, and other travel agents. So from the FGD results and interviews, it can help in developing or formulating a better business strategy model for PT KATARDA INDO GLOBAL to improve income performance. Which in the previous strategy was still not optimal in implementing it such as marketing strategies and human resource strategies, besides the last goal is to analyze new business strategies so that sustainability in the tourism industry, PT KATARDA INDO GLOBAL can implement it.Business solutions that will be carried out through TOWS analysis developed from SWOT analysis, after that Company Level, Business Level, and Functional Level Strategy. The implementation of business strategies is carried out within eight months, up to the end of the year or more following the capabilities of the company. With the implementation and business development of this strategy, it expected that PT KATARDA INDO GLOBAL could increase revenue, increase brand awareness, and be able to compete with competitors.Â Keywords: Tourism Industry, PT Katarda Indo Global, Business Strategy